Cover Image. (21st June 2018) - Lee, Sung Ryul; Koo, Bum Hwan; Byun, Geon Young; Lee, Seung Geun; Kim, Myoung Jin; Hong, Soo Kyung; Kim, Su Yeon; Lee, Yu Jin
Abstract : The cover image, by Sung Ryul Lee et al., is based on the Research Article Influence of Internet dissemination on hospital selection for benign surgical disease: A single center retrospective study, https://doi.org/10.1002/hpm.2545 . Photo credit: Su Yeon Kim.